Multi-Site Cross-Site Inter-Rater and Test-Retest Reliability and Construct Validity of the MarkVCID White Matter Hyperintensity Growth and Regression Protocol. - Bahrani, Ahmed A; Abner, Erin L; DeCarli, Charles S; Barber, Justin M; Sutton, Abigail C; Maillard, Pauline; Sandoval, Francisco; Arfanakis, Konstantinos; Yang, Yung-Chuan; Evia, Arnold M; Schneider, Julie A; Habes, Mohamad; et al. (J Alzheimers Dis, 2023)
BACKGROUND: White matter hyperintensities (WMH) that occur in the setting of vascular cognitive impairment and dementia (VCID) may be dynamic increasing or decreasing volumes or stable over time. Quantifying such changes may prove useful as a biomarker for clinical trials designed to address vascular cognitive-impairment and dementia and Alzheimer's Disease. OBJECTIVE: Conducting multi-site cross-site inter-rater and test-retest reliability of the MarkVCID white matter hyperintensity growth and regression protocol. METHODS: The NINDS-supported MarkVCID Consortium evaluated a neuroimaging biomarker developed to track WMH change. Test-retest and cross-site inter-rater reliability of the protocol were assessed. Cognitive test scores were analyzed in relation to WMH changes to explore its construct validity. RESULTS: ICC values for test-retest reliability of WMH growth and regression were 0.969 and 0.937 respectively, while for cross-site inter-rater ICC values for WMH growth and regression were 0.995 and 0.990 respectively. Word list long-delay free-recall was negatively associated with WMH growth (p < 0.028) but was not associated with WMH regression. CONCLUSIONS: The present data demonstrate robust ICC validity of a WMH growth/regression protocol over a one-year period as measured by cross-site inter-rater and test-retest reliability. These data suggest that this approach may serve an important role in clinical trials of disease-modifying agents for VCID that may preferentially affect WMH growth, stability, or regression.

Neuropathologic Correlates of White Matter Hyperintensities in a Community-Based Cohort of Older Adults. - Arfanakis, Konstantinos; Evia, Arnold M; Leurgans, Sue E; Cardoso, Luis F C; Kulkarni, Arman; Alqam, Nabil; Lopes, Lucas F; Vieira, Diego; Bennett, David A; Schneider, Julie A (J Alzheimers Dis, 2020)
BACKGROUND: The association of white matter hyperintensities (WMH) with age-related vascular and neurodegenerative pathologies remains incompletely understood. OBJECTIVE: The objective of this work was to elucidate the neuropathologic correlates of WMH in a large community-based cohort of older adults. METHODS: Cerebral hemispheres from 603 community-based older adults were imaged with MRI ex vivo. All participants underwent annual clinical evaluation, cognitive assessment, and neuropathologic examination. WMH burden was assessed using a modified Fazekas rating scale. Multiple ordinal logistic regression was used to test the association of WMH burden with an array of age-related neuropathologies, adjusting for demographics. Mixed effects models of cognition controlling for neuropathologies and demographics were used to determine whether WMH burden contributes to cognitive decline beyond measured pathologies. RESULTS: WMH burden in the whole group was associated with both vascular and Alzheimer's disease (AD) pathologies: arteriolosclerosis (p < 10-4), gross (p < 10-4), and microscopic infarcts (p = 0.04), and amyloid-β plaques (p = 0.028). In non-demented participants (mild or no cognitive impairment) (N = 332), WMH burden was related to gross infarcts (p = 10-4) and arteriolosclerosis (p < 10-4), but not to AD pathology. Similarly, in those with no cognitive impairment (N = 178), WMH burden was related to gross infarcts (p = 8×10-4) and arteriolosclerosis (p = 0.014). WMH burden was associated with faster decline in perceptual speed in both the whole (p = 0.038) and non-demented (p = 0.006) groups. CONCLUSION: WMH burden has independent associations with vascular pathologies in older adults regardless of clinical status, and with AD pathology later in the progression of AD. Moreover, WMH burden may reflect additional tissue injury not captured with traditional neuropathologic indices.